Scalable corrective security-constrained economic dispatch considering conflicting contingencies. (June 2018) - Yu, Yaowen; Luh, Peter
Highlights: A new contingency filtering approach can keep or remove conflicting contingencies. Novel warm-start of subproblem models and parallel computing enhance the performance. The Polish 2383-bus system with transmission contingencies is solved in two minutes. Abstract: Reliability is an overriding factor in power system operations. Corrective security-constrained economic dispatch (SCED) satisfying the " N  − 1" criterion is difficult because of a large number of contingencies and the strict time limits for real-time operations. The existence of conflicting contingencies further complicates the problem. To overcome these difficulties, this paper develops a new iterative contingency filtering approach to manage " N  − 1" transmission and generator contingencies via decomposition and coordination. Instead of always removing conflicting contingencies as in existing papers, we offer system operators an important option to keep them for increased reliability, enabled by identifying multiple conflicting contingencies simultaneously. To satisfy the strict time requirements in real-time operations, the computational performance of our approach is significantly enhanced by novel warm-start of subproblem models and by parallel computing. Numerical results demonstrate that our new approach is computationally efficient and scalable, and increases the system reliability. In particular, the Polish 2383-bus system with all transmission contingencies is solved within two minutes.